Integrating indigenous games into preservice teachers' decolonised curriculum practice to help understand economics principles - Mphuthi, Mochina (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Incorporating indigenous knowledge into curriculum practice is essential for fostering a decolonised approach to education, particularly in the context of Economics Education. This study explores how the Morabaraba game, a traditional African board game, can be utilised as a pedagogical tool to teach pre-service teachers complex economic principles. This study aims to demonstrate the potential of indigenous games to promote critical thinking and problem-solving skills within Economics Education, challenging conventional Eurocentric teaching methods. The Africana Framework, which supports decolonised curriculum practices by centring African knowledge systems, underpins this research. This theoretical perspective highlights the importance of integrating local cultural elements into education to enhance learning experiences and foster inclusivity. A case study using qualitative methods was employed with ten purposefully sampled economics and management sciences pre-service teachers. The participants engaged in Morabaraba gameplay during their Economics calculation tasks. Data were collected through observations combined with group discussions to understand how pre-service teachers experienced their learning process. Using the Morabaraba board game during the learning allowed pre-service teachers an opportunity to master the necessary economic principles and calculations while fostering interaction with the material and promoting teamwork practices. Through this method, abstract economic principles became more understandable to pre-service teachers while they discovered ways in which their traditional indigenous knowledge linked to current educational practices. Learning environments are enhanced when indigenous games are integrated into the curriculum. The sustained use of indigenous knowledge systems is recommended to supplement decolonised curriculum practices in higher education institutions.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9, 2025
Keywords: Africana Framework; Curriculum practice; Decolonisation; Morabaraba board game; Pre-service teachers; Education; Curriculum change; Economics -- Study and teaching; Ethnoscience; College teaching -- Methodology; Education higher, South Africa